Status Besi dan Kualitas Diet pada Wanita Usia Subur Pranikah Obesitas di Kota Semarang - Sekar Ratry Nurramadhani; Fillah Fithra Dieny; Etisa Adi Murbawani; A Fahmy Arif Tsani; Deny Yudi Fitranti; Nurmasari Widyastuti (Amerta Nutrition, 2019)
Background: Women of reproductive age are potentially to have double-burden malnutrition due to poor diet quality. Obesity-related anemia affects iron homeostasis (hypoferremia) through low-grade inflammation.Objectives: This study aimed to analyze the differences of iron status among women of reproductive age based on obesity status and diet quality based on iron and obesity status.Methods: A cross-sectional study of female students, aged 18-22 years old that classified as obese (n=25) and non-obese (n=25). Subjects were selected by proportional random sampling. This study used iron status and diet quality as variable datas. Blood samples were taken to determined iron status (Fe serum). Diet quality was analyzed by SQ-FFQ and DQI-I. Statistical analysis using Independent-T Test, One-way ANOVA, Kruskal Wallis, Mann Whitney tests.Results: There were 20% of obese subjects had low iron status and majority (94%) had low diet quality score (52.04±5.2). Iron status of obese women (83.9±20.7 µg/dl) significantly differed to non-obese women (99.2±26.1 µg/dl), p=0.027. Obese group with low iron status had lower diet quality and moderation component score, however adequacy score was higher than other groups, p<0.05. There were no significant differences in variation and overall balance among all groups, p>0.05.Conclusions: Iron status of obese women was significantly different than non-obese women. Obese group with low iron status had lower diet quality and moderation component score, however adequacy score was higher than other groupsABSTRAKLatar Belakang: Wanita Usia Subur (WUS) rentan terkena masalah gizi ganda akibat kualitas diet yang buruk. Obesitas terkait anemia disebabkan inflamasi tingkat rendah yang mempengaruhi homeostasis zat besi (hipoferrimia). Tujuan: Penelitian ini bertujuan untuk menganalisis perbedaan status besi WUS berdasarkan status obesitas, dan perbedaan kualitas diet berdasarkan status besi dan obesitas. Metode: Penelitian ini menggunakan desain cross-sectional, dengan subjek mahasiswi berjumlah 25 orang obesitas dan 25 orang non-obesitas, dipilih menggunakan teknik proportional random sampling. Data yang diambil berupa status besi (kadar Fe serum) melalui pengambilan sampel darah, dan kualitas diet menggunakan wawancara SQ-FFQ dan analisis DQI-I. Analisis menggunakan uji Independent-T Test, One-way ANOVA, Kruskal Wallis, dan Mann Whitney.Hasil: Sebanyak 20% WUS obesitas memiliki status besi rendah dan mayoritas subjek (94%) memiliki kualitas diet rendah (52,04±5,2). Status besi WUS obesitas (83,9±20,7µg/dl) berbeda signifikan dibandingkan WUS non-obesitas (99,2±26,1µg/dl), p=0,027. Kelompok WUS obesitas dengan status besi rendah memiliki skor kualitas diet dan komponen moderasi lebih rendah, namun memiliki skor kecukupan lebih tinggi dibandingkan kelompok lainnya, p<0,05. Komponen variasi dan keseimbangan keseluruhan pada semua kelompok tidak menunjukkan perbedaan signifikan, p>0,05.Kesimpulan: Status besi WUS obesitas signifikan lebih rendah dibandingkan WUS non-obesitas. Kelompok WUS obesitas dengan status besi rendah memiliki skor kualitas diet dan moderasi lebih rendah, namun memiliki skor kecukupan lebih tinggi dibandingkan kelompok lainnya.